Chemical Properties of Sago Grub (Rhynchophorus ferrugineus) Protein Concentrate With Different Initial Drying Method - Mizel A Y Talakua; Helen C D Tuhumury; Priscillia Picauly (Jurnal Agrosilvopasture-Tech, 2023)
The sago grub (Rhychophorus ferrugineus) is a kind of edible insect which can be utilized as an substitute source of protein in the form of concentrates. The extraction process of protein concentrate requires a proper drying technique for the starting material. This study was intended to determine the appropriate initial drying method for sago grub to produce protein concentrates with good chemical properties. In this study, cabinet dryer, sun, and oven drying methods were used to extract sago caterpillar protein concentrate with a block randomized design. The variables observed were the moisture, ash, protein, and fat contents of the sago grub protein concentrate. The results demonstrated that cabinet dryers are the most appropriate drying method for producing protein concentrate with the best chemical and functional characteristics. The drying method of the cabinet dryer produces a protein concentrate with a moisture content of 23%, an ash content of 11.26%, a protein content of 55.37%, and a fat content of 7.67%.